HUBUNGAN DUKUNGAN KELUARGA TERHADAP TINGKAT STRES PADA SISWA SMA DALAM PEMBELAJARAN DARING DI MASA PANDEMI COVID-19 (STIKES Telogorejo Semarang, 2022)
Academic stress occurs because of a pressure experienced by someone with various academic demands. Family support is support thatgiven the closest people, loved ones and respected individuals concerned.The Covid-19 pandemic forced the government to issue rules regarding online learning for students, but online learning has an effect of academic stress on students and therefore family support is important, as a way to prevent and reduce academic stress on students. This research aims toanalyzed the relationship between family support and stress levels in high school students in online learning during the covid-19 pandemic. This research is a descriptive correlational study with a cross sectional approach. The population in this study were students of SMA Negeri 1 Batangan class XI and XII, totaling 96 students. Sampling was done by total sampling technique, so that the sample used was a total of 96 students from the population. The data collection instrument used was a questionnaire. Data analysis was performed by univariate analysis (frequency distribution) and bivariate analysis by spearman rank test. The results showed that there is a significant and negative relationship between family support and stress levels in high school students in online learning during the Covid-19 pandemic with a significance value of p value = 0.000 < 0.05 and an r value of -0.518.